Intelligent Control of High Gain Improved Zeta Converter for Hybrid Renewable Energy Management - Siddheswar Kar; Manish Jain; Murali Matcha (Universitas Ahmad Dahlan, 2026)
The appropriate way to diminish greenhouse gas emissions is the usage of Renewable Energy Sources (RES). Nevertheless, the sporadic nature of these resources has led to random characteristics in the generation and load balancing the microgrid systems. This work proposes an advanced hybrid energy management system that incorporates PV and wind systems with battery to assure continuous supply of power. The system integrates an innovative High Gain Improved Zeta Converter (HGIZC) for effective PV energy conversion, allowing high step-up voltage gain with reduced losses. The HGIZC converter uses voltage multiplier cell that enables it to attain maximum voltage efficiently with decreased component stress. A Chaotic Bacterial Foraging Optimized Proportional Integral (CBFO-PI) controller is developed to dynamically manage the converter output and sustain a stable DC bus voltage. The chaos theory is utilized in CBFO to alter the PI controller’s parameters to sustain a steady voltage. The Wind Energy Conversion System (WECS) utilizes a Doubly Fed Induction Generator (DFIG) coupled with a rectifier to extract maximum energy from wind resources. The benefit of battery is store the power produced by the hybrid energy systems and the bi-directional converter performing charging/discharging function of battery. This research is implemented in MATLAB tool, exposes the converter efficacy of 98.03% with reduced THD 1.03 %. The developed research optimizes power flow among PV, wind and battery systems, assuring stability and allowing reliable hybrid renewable energy integration, thereby efficiently alleviating the variability caused by the sporadic nature of renewable sources.